Disentangling Capabilities for Industry 4.0 - an Information Systems Capability Perspective - Rocco Huber; Anna Maria Oberländer; Ulrich Faisst; Maximilian Röglinger (Information Systems Frontiers, 2022)
Digital technologies revolutionise the manufacturing industry by connecting the physical and digital worlds. The resulting paradigm shift, referred to as Industry 4.0, impacts manufacturing processes and business models. While the 'why' and 'what' of Industry 4.0 have been extensively researched, the 'how' remains poorly understood. Manufacturers struggle with exploiting Industry 4.0's full potential as a holistic understanding of required Information Systems (IS) capabilities is missing. To foster such understanding, we present a holistic IS capability framework for Industry 4.0, including primary and support capabilities. After developing the framework based on a structured literature review, we refined and evaluated it with ten Industry 4.0 experts from research and practice. We demonstrated its use with a German machinery manufacturer. In sum, we contribute to understanding and analysing IS capabilities for Industry 4.0. Our work serves as a foundation for further theorising on Industry 4.0 and for deriving theory-led design recommendations for manufacturers.
Keywords: 000; Industry 4.0; Fourth industrial revolution; Information systems capabilities; Capability framework